ANALISIS KEPEMIMPINAN, ETOS KERJA, DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KOPKAR PT GUDANG GARAM, TBK “MEKAR” KEDIRI - Putri, Arum Eka Refany; Muslih, Basthoumi; Soedjoko, Dodi Kusuma Hadi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
In the current era, companies need to improve employee performance qualifications in order to compete in increasingly fierce business competition. Employee performance is influenced by several factors that can influence it, including leadership, work ethic, and work discipline. This study aims to analyze the influence jointly or partially between leadership, work ethic and work discipline on employee performance at Kopkar PT Gudang Garam Tbk, "MEKAR" Kediri. This research uses quantitative methods with classical assumption test, multiple linear regression, t test, f test, coefficient of determination, sampling technique is simple random sampling using SPSS version 23 application. This study uses Kopkar Mekar employees as a population of 144 people, and obtained a sample of 59 people with the slovin formula. The conclusions obtained are (1) leadership does not have a strong negative effect on employee performance. (2) there is a strong influence between work ethic on employee performance. (3) there is a strong influence between work discipline on employee performance. (4) leadership, work ethic and work discipline have a simultaneous effect on the performance of Kopkar MEKAR Kediri employees.